Bibliographic Review: Libro “La gestión y el desarrollo organizacional: Marco para mejorar el desempeño del capital humano” - Pelekais, Elmar Aldrin (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2022)
In the book "Management and organizational development: Framework to improve the performance of human capital", written by Jorge Alejandro Silva Rodríguez de San Miguel, in 2018, a series of contents related to the subject are developed in 124 pages, which are arranged as follows:The management of organizations, of any line of business, requires that the human capital in the organizations performs in the best possible way. In practice, this is complicated, depending on the type of organization and its degree of complexity (in terms of its line of business, size, organizational climate, among others).